Type IV acromioclavicular joint separation in a collegiate basketball player - Ronchetti, G. M.; Welch, C. A.; Smith, B. I.; Blair, D. E. (International Journal of Athletic Therapy & Training, 2016)
A 19-year-old female basketball athlete sustained a right shoulder injury during collegiate competition resulting from a collision causing severe pain and discomfort. The patient was diagnosed with a unique type IV acromioclavicular (AC) separation. Surgical stabilization of the AC joint and slow progression in rehabilitation with immobilization assisted in protecting the reconstruction. Accurate diagnosis and appropriate intervention helped to lead to the successful recovery and return to play for this patient. There are few cases of type IV acromioclavicular separation reported in the literature and none related to basketball. This case presents the challenges related to the diagnosis and rehabilitation following surgical reconstruction of a type IV acromioclavicular separation.